Au-Catalyzed Piperidine Synthesis via Tandem Acyloxy Migration/Intramolecular [3 + 2] Cycloaddition of Enynyl Esters - Zheng, Huaiji; Huo, Xing; Zhao, Changgui; Jing, Peng; Yang, Juan; Fang, Bowen; She, Xuegong (Organic letters, 2011)
An Au-catalyzed tandem protocol involving enynyl ester isomerization and subsequent intramolecular [3 + 2] cyclization has been developed. This strategy provides an efficient approach for the synthesis of polyfunctional piperidines, which are subunits of many bioactive molecules.